Legal Relevance of the Purpose of Contract in German Law - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Unlike the French Civil code, the German Civil code belongs to the group of so-called anti-causalistic codifications, since it explicitly does not govern the issue of purpose (cause) of contract. Due to this very reason, the delineation between abstract and causal juridical acts gains special importance in German law. The German Civil Code governs a number of juridical acts and other acts of legal importance that are abstract in their nature. Among them the abstract nature of the promise to fulfill an obligation (Schuldversprechung) and the acknowledgement of a debt (Schuldannerkennung) is traditionally considered the most prominent. However, the relation to the purpose for which they are concluded is not entirely interrupted, since in the case of frustration of their purpose, any asset given to the other party is subject to restitution under the rules of unjustified enrichment. The fact that the issue of purpose of contract is not explicitly governed in the German Civil Code, does not lead to the conclusion, though, that it is legally irrelevant. It gains legal relevance in two different aspects: as a licit and as an illicit purpose. On the one hand, juridical acts concluded with the aim to achieve illicit purposes are considered void, for which the Code’s sections on the general confines of the principle of freedom of contract serve the statutory basis - such juridical acts infringe the institution of “good customs” (gute Sitten), usually referred to as public policy, while the performance of other factual or legal acts in order to achieve illicit purposes are sanctioned under the rules of unjustified enrichment. On the other hand, lawful purposes of the parties gain legal relevance in relation to a range of various institutions. Concerning some of them the Code itself contains formulations implying the necessity to ascertain the purpose of contract, while in other cases the case law and the doctrine have come to such conclusion. The determination of the purpose of contract in the context of these institutions either secures the fulfilment of the purpose of assumption of contractual obligation of one of the parties or rectifies the consequences of the frustration of the fulfilment of that purpose. In this range surely the most important institutions are the collapse of the basis of transaction or frustration of purpose (Störung der Geschäftsgrundlage), a special case of discharge of contract due to impossibility, whereby the purpose of contract is realized without the performance of debtor’s obligation, a special case of unjustified enrichment due to frustration of the result aimed by the purpose of the transaction and the invalidity of standard business terms that jeopardize the fulfillment of the purpose of contract.